Thromboxane receptor stimulation associated with loss of SKCa activity and reduced EDHF responses in the rat isolated mesenteric artery. - Crane, G; Garland, C (2004)
1. The possibility that thromboxane (TXA(2)) receptor stimulation causes differential block of the SK(Ca) and IK(Ca) channels which underlie EDHF-mediated vascular smooth muscle hyperpolarization and relaxation was investigated in the rat isolated mesenteric artery. 2. Acetylcholine (30 nm-3 microm ACh) or cyclopiazonic acid (10 microm CPA, SERCA inhibitor) were used to stimulate EDHF-evoked smooth muscle hyperpolarization. In each case, this led to maximal hyperpolarization of around 20 mV, which was sensitive to block with 50 nm apamin and abolished by repeated stimulation of mesenteric arteries with the thromboxane mimetic, U46619 (30 nm-0.1 microm), but not the alpha(1)-adrenoceptor agonist phenylephrine (PE). 3. The ability of U46619 to abolish EDHF-evoked smooth muscle hyperpolarization was prevented by prior exposure of mesenteric arteries to the TXA(2) receptor antagonist 1 microm SQ29548. 4. Similar-sized smooth muscle hyperpolarization evoked with the SK(Ca) activator 100 microm riluzole was also abolished by prior stimulation with U46619, while direct muscle hyperpolarization in response to either levcromakalim (1 microm, K(ATP) activator) or NS1619 (40 microm, BK(Ca) activator) was unaffected. 5. During smooth muscle contraction and depolarization to either PE or U46619, ACh evoked concentration-dependent hyperpolarization (to -67 mV) and complete relaxation. These responses were well maintained during repeated stimulation with PE, but with U46619 there was a progressive decline, so that during a third exposure to U46619 maximum hyperpolarization only reached -52 mV and relaxation was reduced by 20%. This relaxation could now be blocked with charybdotoxin alone. The latter responses could be mimicked with 300 microm 1-EBIO (IK(Ca) activator), an action not modified by exposure to U46619. 6. An early consequence of TXA(2) receptor stimulation is a reduction in the arterial hyperpolarization and relaxation attributed to EDHF. This effect appears to reflect a loss of SK(Ca) activity.